Intervening Effect of Financial Services on the Relationship Between Bank Restructuring and Financial Performance - Angela Mucece Kithinji; Mirie Mwangi; Kate Litondo; Martin Ogutu (European Scientific Journal, ESJ, 2017)
Previous studies on the relationship between bank restructuring and financial performance reveal conflicting results with few studies establishing the effect of financial services. Few studies have investigated the causality between bank restructuring and financial performance as intervened by deposits and customer loans. The positivism research philosophy and descriptive and inferential causal research design were used in this study. The hypothetical view of the study was that the relationship between bank restructuring and financial performance of commercial banks in Kenya is not intervened by deposits and customer loans. The 39 commercial banks that were consistently in business for the period 2002 to 2014 were included in the study. Bank restructuring was disaggregated into financial restructuring, capital restructuring, operational restructuring and asset restructuring. The empirical findings were as follows: There was a significant direct association between bank restructuring and financial performance which was intervened by deposits and customer loans as proxies for financial services. Deposits were found to be significant in intervening the relationship between bank restructuring and financial performance. Customer loans on the other had was not found to significantly intervene the relationship between bank restructuring and financial performance. A composite variable of financial services denoting the aggregate of the intervention of deposits and customer loans showed a significant intervening effect on the relationship between bank restructuring and financial performance. The study outcome therefore reveals that the hypothesis that the relationship between bank restructuring and financial performance is not intervened by financial services is rejected. The conclusion is that banks should focus more on deposits to caution against a decrease in financial performance. Additionally customer loans should not be ignored since the intervention though insignificant tends to negatively influence financial performance. The implication is that when banks focus more on the provision of financial services they are likely to compromise financial finance possibly because of the increased costs associated with providing financial services. Regulatory institutions such as the Central Bank of Kenya (CBK) and the Kenya Institute of Bankers can use the study results to enhance policy and prudential guidelines to increase profitability of the banks. The study recommends that there is need to increase financial services offered by banks to increase outreach other than improving profitability of banks.